APROXIMANDO O ENSINO DE CONFORTO TÉRMICO ÀS FERRAMENTAS BIM ATRAVÉS DE RECURSOS DE APRENDIZAGEM - Rosa, Artur Hugo da; Pereira, Alice Theresinha Cybis; Pereira, Fernando O. Ruttkay (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The Internet, with Virtual Learning Environments (VLE), enables learning to take place in many ways. One of them is through Learning Objects (LO). This paper presents the development of a LO in the area of thermal comfort using BIM software. The object is called "Solar Study in Revit" and is available through the TEAR_AD (A Network of Teaching and Learning Technology in the areas of Architecture and Design). The methodology was elaborated in four parts: the elaboration of the exercise based on PANCA (Environmental Comfort Analysis Practices), the choice of the methodological approach for the exercise, the structure of the LO and the application and test. The LO was very didactic and brought positive results, being a contribution to avoid future errors of digital simulation.